La construction des territoires nationaux latino-américains vue depuis leurs marges - Pedro Navarro Floria (Les Cahiers ALHIM)
Each of the Latin American States built its space domination, between the nineteenth and twentieth centuries, extending through military conquest, missions or other strategies to a variety of « national territories ». The type of relationship that each state has since established with those marginal spaces, it is illustrative of the functions that the territory -and particularly its borders- plays both in relation to the nationalism of the past with the current integration processes, because of which some of those spaces soon be marginal -bordering neighboring states- become central or cause, at least, renewed attention on them. We propose a comparative look on the processes of territorial formation of Latin American countries, enabling us to better understand the current and future territorial problems in the region.